The Competitive Edge of Sustainability Operational Management as a Driver of Firm Value - S, James Leri; Sumayku, Imelda Regina; Soputan, Fibrillya Priskila Moreen; Lule, Benny (Jurnal Informatika Ekonomi Bisnis, 2025)
Sustainability has emerged as a key factor to enhance a firm's competitive advantage. The role of operations management in achieving sustainability business practices that bring firm value remains to be studied. By means of a Systematic Literature Review approach, this paper discusses the role operations management plays in creating firm value for its competitive strategies and globalization strategy. Findings of this research indicate that firms can enjoy better financial performance from higher integration environmental practices in their day-to-day business practices. An improved reputation, brand recognition among customers and increased confidence among stakeholders will result. However, effective operations management is more efficient in use of resources and thereby lower costs or environmental footprints. This suggests those results that sustainability is not simply a demand for compliance but an asset which helps make companies more competitive in the long term. This means companies should strive to strengthen operational sustainability management at all times if they are to gain the most and best firm value in dynamic, fast-moving markets.